Level of human trafficking management competency among the municipal executives in the first district of Biliran province. - Coco, Niña Jedelyn (Niña Jedelyn Coco [and] Michael Montes Gabing, 2010)
This is a descriptive study of the level of human trafficking management competency of the three municipal executives in the First District of Biliran Province. The objectives of this study includes: 1.) to identify the socio-demographic profile of the municipal executives, 2.) to determine the level of human trafficking management competency among municipal executives based on their own perception, 3.) to determine the level of human trafficking management competency among municipal executives as perceived by the household heads, 4.) to identify if there is a significant difference between the municipal executives' own assessment in their own level of competence and the household heads perception regarding their municipal executives' level of competence and 5.) to determine the relationship between socio-demographic profile of the municipal executives and their level of human trafficking management competency as perceived by the household heads.